Enhancing clinical diagnosis for patients with persistent pulmonary abnormalities after COVID-19 infection: the potential benefit of 68 Ga-FAPI PET/CT - Sviridenko, Anna; Boehm, Anna; di Santo, Gianpaolo; Uprimny, Christian; Nilica, Bernhard; Fritz, Josef; Giesel, Frederik L.; Haberkorn, Uwe; Sahanic, Sabina; Decristoforo, Clemens; Tancevski, Ivan; Widmann, Gerlig; et al. (Clinical nuclear medicine, 2022)
Coronavirus disease 2019 (COVID-19)-related pneumonia challenges clinical practice. We explore the potential diagnostic benefit of PET/CT to establish the underlying inflammatory or fibrotic repair processes in prolonged structural lung abnormalities in COVID-19 patients. - Patients and Methods - Six post COVID-19 patients suspected for pulmonary fibrosis were scheduled for dual-tracer PET/CT with 18F-FDG and 68Ga-fibroblast activation protein inhibitor (FAPI)-46. The uptake of 68Ga-FAPI-46 in the involved lung was compared with a control group of 9 non-COVID-19 patients. Clinical data and PET/CT imaging were collected and analyzed. - Results - PET/CT revealed in all 6 pulmonary impaired patients the reduced glucose avidity on 18F-FDG and clear positivity on 68Ga-FAPI-46 PET/CT in comparison to the control group. - Conclusions - Enhancing fibrotic repair mechanisms, 68Ga-FAPI PET/CT may improve noninvasive clinical diagnostic performance in patients with long-term CT abnormalities after severe COVID-19. Although this study shows promising results, additional studies in larger populations are required to establish a general diagnostic guideline.